Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.1262/jrd.09-085h
|View full text |Cite
|
Sign up to set email alerts
|

How to Repair the Oocyte and Zygote?

Abstract: Abstract. The supply of human oocytes is very limited. This restricts not only certain assisted reproduction procedures in IVF clinics where recipients wait for oocytes from donors, but also development of some promising approaches, like therapeutic nuclear transfer with subsequent derivation of patient compatible embryonic stem cells. Moreover, in some patients, collected oocytes exhibit certain specific defects, and logically, we can expect that after fertilization, the embryos arising from these defective o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…In contrast, however, the oocytes in degenerating primordial follicles exhibit dense ZP2 expression throughout the nucleus and ooplasm (black asterisk, panel A). Nuclear and zona pellucida abnormalities and cytoplasmic defects were reported in altered oocytes (Fulka et al, 2009).…”
Section: A Proportionality Of Resting Degenerating and Growing Primmentioning
confidence: 99%
“…In contrast, however, the oocytes in degenerating primordial follicles exhibit dense ZP2 expression throughout the nucleus and ooplasm (black asterisk, panel A). Nuclear and zona pellucida abnormalities and cytoplasmic defects were reported in altered oocytes (Fulka et al, 2009).…”
Section: A Proportionality Of Resting Degenerating and Growing Primmentioning
confidence: 99%
“…Indeed, a recent study by Wells et al , 16 with improved media technology, has identified that over 40% of blastocysts are still chromosomally abnormal, and that, contrary to previous findings, most monosomies can reach the blastocyst stage 16–20 . Moreover, other important factors, such as mitochondrial RNA activity and the bottleneck female origin of mitochondrial transmission, are involved in oocyte competence and could be involved in the aging process, directly influencing the meiotic and mitotic process 5–7 …”
Section: Aging Implantation and Abnormal Embryosmentioning
confidence: 97%
“…[16][17][18][19][20] Moreover, other important factors, such as mitochondrial RNA activity and the bottleneck female origin of mitochondrial transmission, are involved in oocyte competence and could be involved in the aging process, directly influencing the meiotic and mitotic process. [5][6][7] Embryo-endometrial interactions The endometrial role has been evaluated by investigating the contributions of inflammatory factors: adhesion molecules such as integrins, 21 pinopodes, 22 leukemia inhibiting factor (LIF), 23 proteomics, 24,25 metabolomics, 26 and, recently, by studies into the regulatory effect of preimplantation factor (PIF). 27,28 Emerging from this evidence is that endometrial modifications by the embryo, and between the many players involved with the embryo, have a guiding role.…”
Section: Aging Implantation and Abnormal Embryosmentioning
confidence: 99%
See 1 more Smart Citation
“…These and other data suggest that sperm with poor DNA quality persist in washed sperm preparations from fertile and infertile men [8][9][10][11][12][13] and unlike IVF, where there is a natural selection by the egg, ICSI could be particularly vulnerable to a poor choice of sperm. We and others have reported that sperm DNA fragmentation is a risk factor for miscarriage in ICSI treatment 14,15 and this may result from an oocyte-mediated DNA repair process [16][17][18][19] that provides adequate support from fertilisation to clinical pregnancy (CP) (hence the lack of an association between DNA fragmentation and CP in ICSI compared with IVF), but may be inadequate to sustain it beyond CP with resulting pregnancy loss. By eliminating abnormal sperm from the sample preparation for ICSI, success rates could theoretically be improved.…”
Section: Introductionmentioning
confidence: 99%